2019
DOI: 10.1111/cen.14012
|View full text |Cite
|
Sign up to set email alerts
|

Absence of vitamin D deficiency among common outdoor workers in Delhi

Abstract: Background There is reservation about accepting the notion of widespread vitamin D deficiency (VDD) in sunny countries because information base is largely urban indoors, and the cut‐off serum 25(OH)D > 75.0 nmol/L to define sufficiency is perceived as high. Objective We assessed the vitamin D status of subjects engaged in six types of outdoor jobs with freedom to seek shade, when needed. Design Descriptive observational study. Subjects and methods A total of 573 outdoors, (hawkers, n = 144; auto‐rickshaw drive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
0
8
2
1
Order By: Relevance
“… State/ union territories Case/million Death/million Total no. of healthy subjects Mean 25(OH)D levels (ng/ml) References Andhra Pradesh 5530 50 1936 18 [32] , [33] , [34] , [35] , [36] Assam 2390 6 768 26 [37] , [38] , [39] Bihar 940 4 50 30 [40] Chandigarh 1830 27 878 34 [41] , [42] , [43] , [44] , [45] , [46] Delhi 8970 249 2919 15 [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] Goa 7520 64 …”
Section: Resultsmentioning
confidence: 99%
“… State/ union territories Case/million Death/million Total no. of healthy subjects Mean 25(OH)D levels (ng/ml) References Andhra Pradesh 5530 50 1936 18 [32] , [33] , [34] , [35] , [36] Assam 2390 6 768 26 [37] , [38] , [39] Bihar 940 4 50 30 [40] Chandigarh 1830 27 878 34 [41] , [42] , [43] , [44] , [45] , [46] Delhi 8970 249 2919 15 [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] Goa 7520 64 …”
Section: Resultsmentioning
confidence: 99%
“…Another interesting finding was that females were comparatively less deficient than males, contrary to the expected element of more covered clothing [27], [31], lesser outdoor time [32] and consequently lesser exposure to sunlight [32], [33].…”
Section: Discussionmentioning
confidence: 94%
“…Low sun exposure was identified as another major risk factor for hypovitaminosis D. With availability of near to ample sunlight throughout the year in the country, the heliophobic tendency of South Asian culture [34], sun avoidance behavior [35], fear of tanning [34], indoor working hours [32], lack of deliberate sun exposure [32] and covered clothing [27], [31] could account for the high prevalence of Vitamin D deficiency in Pakistan.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies from India and abroad have shown widely prevalent vitamin D deficiency in patients with T2DM [3,9,10]. On the other hand, various studies have shown that outdoor workers have adequate sunlight exposure, and most of them usually have sufficient serum 25(OH)D levels [14,16,17]. The present study was carried out to assess the vitamin D status of outdoor workers with T2DM -an area where there is a dearth of data not only from India but also globally.…”
Section: Discussionmentioning
confidence: 99%
“…From an Indian perspective, this assumes special significance as about 75% of its total labor force is engaged in outdoor work, including farming and construction activity [15]. There are two studies from North India that looked at outdoor workers in New Delhi and found a considerably low prevalence of vitamin D deficiency [16,17]. A small study from South India also found normal serum 25(OH)D levels in outdoor laborers and fishermen from Thiruvananthapuram [18].…”
Section: Introductionmentioning
confidence: 99%